FCER2 T2206C variant associated with FENO levels in asthmatic children using inhaled corticosteroids: The PACMAN study - Karimi, Leila (Clin Exp Allergy, 2019)
BACKGROUND: The FCER2 gene, via encoding of the CD23 receptor, plays an important role in the regulation of IgE responses. A genetic variant of the FCER2 gene (T2206C) was previously shown to be associated with IgE levels in asthmatic children. IgE sensitization has also been linked to increased levels of fractional exhaled nitric oxide (FENO). OBJECTIVE: To investigate whether the FCER2 T2206C variant influences FENO levels in asthmatic children with a reported use of inhaled corticosteroids (ICS). METHODS: This cross‐sectional study involved 593 asthmatic children with a reported use of ICS, availability of FENO measurements and genotyping data on the FCER2 T2206C variant (rs28364072). An additive genetic model was assumed, and the association between the FCER2 T2206C variant and the log‐transformed (ln) FENO levels was evaluated using linear regression analysis, adjusted for age, sex, adapted British Thoracic Society (BTS) treatment steps and atopy. RESULTS: The mean age of the population was 9.1 ± 2.2 years, and the median of FENO levels was 13.0 ppb with an interquartile range (IQR) of (8.0‐27.5 ppb). The minor allele (G) frequency of rs28364072 was 29.6%, and each extra copy of the G allele was significantly associated with a lower level of the geometric mean of FENO (log scale, β = −0.12, 95% CI: −0.23, −0.02). CONCLUSION AND CLINICAL RELEVANCE: Our results showed that the FCER2 T2206C variant was significantly associated with lower FENO levels in carriers of the G allele. Nevertheless, this SNP contributed little to the variability in FENO levels in this patient population. Our findings contribute to the present knowledge on FENO in asthmatic children; however, future replication studies are required to establish the role of this gene in relation to FENO.